Power and agency: Characterisations of the female victim of family violence. Issue 3 (September 2019) - Kent, Antonia
This article explores the divergence between how female victims of family violence characterise themselves and how they are characterised by the police officers who respond to family violence incidents. It posits the socially constructed nature of female victimhood and how such constructions create totalising discourses which affect policy, community attitudes and even the self-perceptions of abused women. In the following study, Michael Halliday's lexicogrammar theory was applied to public texts from the 2015 Royal Commission into Family Violence to facilitate an investigation into how the names given to the actors in discourse, and the verb processes used to describe the actions of those actors, contribute to the emergence of discourses on power and agency. Although these discourses are used to represent the power dynamics of family violence, they are revealed here to be at odds with the experiences of abused women, who named themselves and their capacity to act in a variety of different, often conflicting, ways. I conclude that new discourses need to be forged which better speak to women's experiences of abuse and respond more effectively and sensitively to their needs.